Design and Development of an Expert System Application for Detecting Cowhide Disease at the UPT Puskeswan Dharmasraya Regency Using the Web-Based Forward Chaining Method: Rancang Bangun Aplikasi Sistem Pakar Pendeteksi Penyakit Kulit Sapi Di UPT Puskeswan Kabupaten Dharmasraya Dengan Menggunakan Metode Forward Chaining Berbasis Web - M. Raziq Sabri (Perkumpulan Doktor Indonesia Maju (PDIM), 2021)
Cattle are livestock that have high economic potential, both as beef cattle, livestock seeds and food ingredients. Cows are a good investment medium because the results can be sold or developed again and then sold at a price that is in accordance with the capital to care for them properly. for sale. Dharmasraya Regency is one of the districts that have the potential for beef cattle development. However, from year to year the cattle population decreases, this happens because of diseases that attack cattle and even the death of livestock and the lack of knowledge of farmers on handling cattle diseases is the main factor in the death of livestock and the lack of veterinarians. Therefore, it is necessary to have a system that can be used by officers and livestock groups to diagnose livestock diseases and find out how to handle them. So that if there are sick animals, they can be directly handled based on the output of the system.Keywords: System, Expert, Computerization, Livestock, Forward Chaining.